(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
The article investigates the character of artistic searching of Yu. Opilskyy in historical fiction of the beginning of twentieth century. The author deals with the inno-vation of the writer in the creation of the national historical novel, particularly in mod-eling of the artistic world view and the image of the character in it, the artist’s historio-sophical thinking identity in the context of intellectual prose of his day.